1996
DOI: 10.1111/j.1469-8749.1996.tb15048.x
|View full text |Cite
|
Sign up to set email alerts
|

School Performance of Elbw Children: A Controlled Study

Abstract: SUMMARY This paper examines the prevalence of learning difficulty in reading, spelling, mathematics and writing and the prevalence of attention deficit disorder (ADD) in extremely low‐birthweight (ELBW) children at school compared to their peers. Parents of 87 eligible ELBW children completed an educational questionnaire and questionnaire for ADD. Teachers of the ELBW children completed a detailed educational and ADD questionnaire for the study child and two control children in the same class, matched for âge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 21 publications
8
36
0
4
Order By: Relevance
“…Some studies of children with VLBW/VPTM suggest more MD and MLD in males than in females (O'Callaghan et al, 1996;Johnson and Breslau, 2000), though other investigations have not found sex differences in this population (e.g., Saigal et al, 2000;Taylor et al, 2000;Grunau et al, 2004). With respect to potential age differences in MD, impairments on tests of mathematics achievement in VLBW/ VPTB cohorts are evident from the early school-age years and persist into adolescence and young adulthood (Saigal et al, 1990;Taylor et al, 1995;Botting et al, 1998;Saigal et al, 2000;Rickards et al, 2001;Hack et al, 2002).…”
Section: Sex and Age Differences In Mathematics Outcomesmentioning
confidence: 99%
“…Some studies of children with VLBW/VPTM suggest more MD and MLD in males than in females (O'Callaghan et al, 1996;Johnson and Breslau, 2000), though other investigations have not found sex differences in this population (e.g., Saigal et al, 2000;Taylor et al, 2000;Grunau et al, 2004). With respect to potential age differences in MD, impairments on tests of mathematics achievement in VLBW/ VPTB cohorts are evident from the early school-age years and persist into adolescence and young adulthood (Saigal et al, 1990;Taylor et al, 1995;Botting et al, 1998;Saigal et al, 2000;Rickards et al, 2001;Hack et al, 2002).…”
Section: Sex and Age Differences In Mathematics Outcomesmentioning
confidence: 99%
“…Furthermore, the authors concluded that specific learning problems and attention deficit tend to co-exist with low IQ score in low birth weight children. In a study by O'Callaghan et al investigating learning and attentional problems in ELBW children compared to a matched control group, it was concluded that school aged ELBW children have a high prevalence of learning difficulty (O'Callaghan et al, 1996). In this particular study, the risk of attention deficit disorder in ELBW children was not increased when compared to the matched control children.…”
Section: Impact Of Preterm Birth On Cognition Behaviour and Learningmentioning
confidence: 57%
“…However, the possible link between maternal factors and neurodevelopmental outcomes has been challenged by O'Callaghan et al, who found that maternal education, maternal age and marital status were not significantly related to later learning difficulty in ELBW children (O'Callaghan et al, 1996). Additionally, Sommerfelt et al found that there were environmental and biological factors that had little influence on later behavioural problems in a study of five year old LBW children (Sommerfelt, Troland, et al, 1996).…”
Section: Environmental Factorsmentioning
confidence: 96%
See 2 more Smart Citations